2022
DOI: 10.1186/s12864-022-08874-1
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide detection of copy number variation in American mink using whole-genome sequencing

Abstract: Background Copy number variations (CNVs) represent a major source of genetic diversity and contribute to the phenotypic variation of economically important traits in livestock species. In this study, we report the first genome-wide CNV analysis of American mink using whole-genome sequence data from 100 individuals. The analyses were performed by three complementary software programs including CNVpytor, DELLY and Manta. Results A total of 164,733 CN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 145 publications
0
8
0
1
Order By: Relevance
“…The TOX gene, located in the duplication CNVR75 (Chr4:75,332,844,330–75,473,471), which overlapped with the identified CNVR in our previous study in American mink 64 , was significantly associated with FBW and ADG. The TOX gene is a family member of high‐mobility group box proteins and serves as a regulator of gene expression, mostly through modifying the density of the chromatin structure 65 .…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…The TOX gene, located in the duplication CNVR75 (Chr4:75,332,844,330–75,473,471), which overlapped with the identified CNVR in our previous study in American mink 64 , was significantly associated with FBW and ADG. The TOX gene is a family member of high‐mobility group box proteins and serves as a regulator of gene expression, mostly through modifying the density of the chromatin structure 65 .…”
Section: Discussionmentioning
confidence: 57%
“…Regarding the female reproduction traits, we found 168 significant CNVRs, overlapping with several functional genes, among which GRM1, RNASE10, WNT3, WNT3A, and WNT9B might be the candidate genes related to female reproduction in mink. The GRM1 gene, which was previously identified in a CNV study in American mink 64 , was located within the duplication CNVR15 (Chr1: 56,870,177–56,925,961), associated with AWB trait. The GRM1 was a gene of interest reported in several studies to be associated with female reproduction in different livestock species, such as seasonal reproduction in sheep 79 , litter size in goats 80 , number of teats and litter traits in pig 81 , and fertility-related traits in cattle 82 .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The increased gene expressions in the oviductal magnum indicated that they actively participated in the synthesis of egg albumen in laying hens fed with RE. According to KEGG enrichment analysis, four pathways were signi cantly enriched in the RE200 group, which were closely associated with immune response (relaxin signaling pathway) [46], albumen formation and secretion (focal adhesion and ECM-receptor interaction) [43], and behavior (circadian entrainment) [47]. Collectively, RNA-seq data showed that RE improved gene expressions and functional pathways related to immune function and albumen formation in the oviductal magnum, which provided a direct molecular mechanism for improvements in egg albumen of laying hens induced by RE supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in humans with about 69 detection algorithms for SV revealed that Manta is better than most software [ 40 ]. Pourya et al found characteristics-related genes in mink by using Manta [ 41 ]. A total of 15,972 and 20,774 CNVs were identified in WBP and AWB, separately.…”
Section: Discussionmentioning
confidence: 99%